PENGARUH PEMBERIAN EKSTRAK MORINGA LEAVES TERHADAP KENAIKAN KADAR HEMOGLOBIN PADA IBU HAMIL DI WILAYAH KERJA PUSKESMAS BLUTO: Effect Of Administration Of Moringa Leaves Extract On Increasing Hemoglobin Levels In Pregnant Women In The Working Area Of Bluto Health Center - Kurniyati, Eka Meiri; Mulyadi, Eko; Musa NF, Lina (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2024)
Iron deficiency always occurs in pregnant women. Moringa leaves can increase hemoglobin levels because they contain iron, folic acid, vitamin A and vitamin C. The research aims to analyze the impact of giving Moringa leaf extract on increasing hemoglobin levels in pregnant women. This research is a quantitative study with a quasi eksperimen design using the one group method. pre-test post-test. The population was 72 pregnant women. The sample was selected using a random sampling technique, obtaining 19 respondents for the control group and 19 respondents for the treatment group. The results of the study showed that hemoglobin levels in pregnant women before administering Moringa leaf extract had an average of 10.4 gr%, while after administration it had an average of 11.5 gr%. The statistical test results show a p-value of 0.000 (p<?), which indicates that there is a significant effect of administering Moringa leaf extract on increasing hemoglobin levels in pregnant women. Therefore, it is recommended for pregnant women to consume vegetables that are rich in iron such as Moringa leaves.